Immunogenicity and Safety of a Novel 13-Valent Pneumococcal Vaccine in Healthy Chinese Infants and Toddlers - Zhao, Yuliang; Li, Guohua; Xia, Shengli; Ye, Qiang; Yuan, Lin; Li, Hong; Li, Jiangjiao; Chen, Jingjing; Yang, Shuyuan; Jiang, Zhiwei; Zhao, Guoqing; Li, Rongcheng; et al. (Frontiers in Microbiology, 2022)
Background To determine the non-inferiority of the 7 common serotypes (4, 6B, 9V, 14, 18C, 19F, and 23F) in the pneumococcal conjugate vaccine (PCV) 13 with each serotype conjugated to a tetanus toxoid carrier protein and adsorbed on aluminum phosphate, and the superiority of its 6 additional serotypes (1, 3, 5, 6A, 7F, and 19A), to the serotypes in the PCV7. Methods Participants were evenly randomized in a 1:1 ratio either into the PCV13 or PCV7 groups, to receive 3 doses of the vaccine at the age of 3, 4, and 5 months, and a booster dose between 12 - 15 months of age. Serotype-specific antibodies were measured using standardized enzyme-linked immunosorbent assay (ELISA) and opsonophagocytic activity (OPA) micro-colony assay method. Results A total of 1040 healthy infants were enrolled. All the 7 common serotypes in the PCV13 were non-inferior to those in the PCV7 in terms of the serotype-specific IgG production induced; however, non-inferiority was not shown for serotype 6B after the infant series. The proportion of subjects who reached OPA antibody titers ≥ 1:8 in the PCV13 group was 89.25% or higher. Local reactions and systemic events were mild or moderate in severity, and similar between the 2 groups. No new safety signals were observed. Conclusions The newly developed PCV13 was immunogenic for all serotypes and had a comparable safety profile to the marketed PCV7.